(3MSf GdJfHg deG hQO aj GdJTHg (B/s - (3fLe GdOjf GdZRj, eMeO Hf eMeO GdYGeQj GdbQTj GdZRj GdOeTbj GdTGaYjs 977-1061 (3gLQj(B.s; (3WGdH, fhQ GdOjfs ((3OeTb (B- (3ShQjG (B:s (3HjQhJ (B- (3dHfGf (B:s (3GdUGdMjI (B- (3GdchjJ (B:s (3OGQ GdfhGOQ ,s, 2011)
(3hgh cJGH aQjO aj HGHg jTJed Ydi HjGf eG jJTHg Hg GdeSde h eG dG jJTHg Hg(B.s
Keywords: (3GdCNdGb GdESdGejI s; (3GdBOGH GdESdGejIs